IMPOLITENESS STRATEGIES BASED ON CULPEPERS MODEL: A DISCOURSE ANALYSIS OF A MAN CALLED OTTO - Theresia, Angelia; Nisa, Baiatun (Sanata Dharma University, 2024)
This research delves into a comprehensive analysis of impoliteness strategies used by Otto, the main character in the movie A Man Called Otto, drawing upon Culpepers model. The objectives encompass the identification of the most common type of impoliteness strategy and the examination of the function associated with each type. Moreover, the qualitative discourse analysis method was used to gain a deeper and more holistic comprehension of the research objectives that encompass a broader context beyond sentences. Within this method, a total of 155 instances of Ottos impolite speech were meticulously examined. The findings revealed two facets: first, there are three types of impoliteness strategies, namely positive impoliteness, negative impoliteness, and withhold politeness. Among these, positive impoliteness emerged as the most frequently used strategy, followed by negative impoliteness and withhold politeness. Second, two functions attributed to the three impoliteness strategies used by the main character are found, namely affective impoliteness and coercive impoliteness.